2020
DOI: 10.1017/s2040174419000850
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors in offspring exposed to gestational diabetes mellitus in utero: systematic review and meta-analysis

Abstract: Gestational diabetes mellitus (GDM) is a pregnancy complication that affects one in seven pregnancies. Emerging evidence demonstrates that children born of pregnancies complicated by GDM may be at increased risk of cardiovascular disease (CVD) in adulthood. Therefore, the aim of this study was to determine cardiovascular risk factors in offspring exposed to GDM in utero. PubMed, CINAHL, SCOPUS, and EMBASE databases were searched. Information was extracted on established CVD risk factors including blood pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 80 publications
0
47
0
Order By: Relevance
“…However, this meta-analysis did not examine maternal effects during gestation. To compensate for this gap, another group performed a meta-analysis to investigate the association between gestational diabetes mellitus and the risk of CVD in children exposed to gestational diabetes mellitus [ 57 ]. They observed that systolic blood pressure, but not diastolic blood pressure, is increased in children exposed to maternal gestational diabetes mellitus compared to those from an otherwise healthy pregnancy [ 57 ].…”
Section: Early Leptin For Future Cardiometabolic Outputmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this meta-analysis did not examine maternal effects during gestation. To compensate for this gap, another group performed a meta-analysis to investigate the association between gestational diabetes mellitus and the risk of CVD in children exposed to gestational diabetes mellitus [ 57 ]. They observed that systolic blood pressure, but not diastolic blood pressure, is increased in children exposed to maternal gestational diabetes mellitus compared to those from an otherwise healthy pregnancy [ 57 ].…”
Section: Early Leptin For Future Cardiometabolic Outputmentioning
confidence: 99%
“…To compensate for this gap, another group performed a meta-analysis to investigate the association between gestational diabetes mellitus and the risk of CVD in children exposed to gestational diabetes mellitus [ 57 ]. They observed that systolic blood pressure, but not diastolic blood pressure, is increased in children exposed to maternal gestational diabetes mellitus compared to those from an otherwise healthy pregnancy [ 57 ]. Not only is leptin in maternal serum and cord blood closely associated with the birth weight of neonates, as aforementioned, but it also has a further role in affecting cardiometabolic fate in later life.…”
Section: Early Leptin For Future Cardiometabolic Outputmentioning
confidence: 99%
“…We thank Dr. Lu and Dr. Wang for their comments regarding our systematic review and meta-analysis on cardiovascular disease in offspring exposed to gestational diabetes mellitus in utero. 1 Their comments highlight important considerations regarding study quality in systematic review and meta-analyses and statistical methods put in place to address low-quality studies.…”
Section: Dear Editormentioning
confidence: 99%
“…We read the paper by Pathirana et al 1 with interest. The authors performed a large metaanalysis to determine cardiovascular risk factors in offspring exposed to gestational diabetes mellitus (GDM) in utero.…”
Section: Dear Editormentioning
confidence: 99%